Genome editing for vegetable crop improvement: Challenges and future prospects - Devi, Ruma; Chauhan, Shivani; Dhillon, Tarsem Singh (Frontiers in Genetics, 2022)
Vegetable crops are known as protective foods due to their potential role in a balanced human diet, especially for vegetarians as they are a rich source of vitamins and minerals along with dietary fibers. Many biotic and abiotic stresses threaten the crop growth, yield and quality of these crops. These crops are annual, biennial and perennial in breeding behavior. Traditional breeding strategies pose many challenges in improving economic crop traits. As in most of the cases the large number of backcrosses and stringent selection pressure is required for the introgression of the useful traits into the germplasm, which is time and labour-intensive process. Plant scientists have improved economic traits like yield, quality, biotic stress resistance, abiotic stress tolerance, and improved nutritional quality of crops more precisely and accurately through the use of the revolutionary breeding method known as clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein-9 (Cas9). The high mutation efficiency, less off-target consequences and simplicity of this technique has made it possible to attain novel germplasm resources through gene-directed mutation. It facilitates mutagenic response even in complicated genomes which are difficult to breed using traditional approaches. The revelation of functions of important genes with the advancement of whole-genome sequencing has facilitated the CRISPR-Cas9 editing to mutate the desired target genes. This technology speeds up the creation of new germplasm resources having better agro-economical traits. This review entails a detailed description of CRISPR-Cas9 gene editing technology along with its potential applications in olericulture, challenges faced and future prospects.